2012
DOI: 10.1007/s10805-012-9148-5
|View full text |Cite
|
Sign up to set email alerts
|

Values and Corporate Social Responsibility Perceptions of Chinese University Students

Abstract: The purpose of this study is to analyse the effects of personal demographic factors on Chinese university students' values and perceptions of Corporate Social Responsibility (CSR) issues, and to identify the link between personal values and perceptions of CSR. The quantitative data consisted of 980 Chinese university students, and were collected by using a structured self-completion questionnaire. This study found that: 1) the importance of values education should be stressed, because we found that altruistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 118 publications
5
46
2
2
Order By: Relevance
“…For both firm size and firm age, the natural logarithm was used to avoid skewed distributions [94,95]. We controlled for the entrepreneur's age because older people perceive CSR negatively [96] while young people are more probable to change their CSR perceptions [97]. Gender was included because it affects firm performance [98].…”
Section: Control Variablesmentioning
confidence: 99%
“…For both firm size and firm age, the natural logarithm was used to avoid skewed distributions [94,95]. We controlled for the entrepreneur's age because older people perceive CSR negatively [96] while young people are more probable to change their CSR perceptions [97]. Gender was included because it affects firm performance [98].…”
Section: Control Variablesmentioning
confidence: 99%
“…Wang and Juslin (2012) Concerns related to the concept of CSR grow as different dimensions are added to it, leading to a lack of consensus about findings; such concerns occupy an important place in the literature (Baden, Harwood, & Woodward, 2009;Fernando, 2010;Fernando & Sim, 2011;Ibrahim et al, 2006;Perrinjaquet et al, 2007;Pomering & Johnson, 2009). Business leaders have also manifested different views about the concept of CSR (Sprinkle & Mainess, 2010).…”
Section: Corporate Social Responsibility and The Triple Bottom Linementioning
confidence: 99%
“…Although research on the relationship between social demographics and value structures can be found in the literature (Wang & Juslin, 2012), few studies have empirically analyzed the influence of the framework of human values on the perception of corporate social responsibility (CSR) in the context of higher education (Rama, Ravenscroft, Wolcott, & Zlotkowski, 2000;Sobczak, Debucquet, & Havard, 2006;Weber, Weber, Sleeper, & Schneider, 2004;Weber & Glyptis, 2000;Wong, Long, & Elankumaran, 2010). Despite the scarcity of studies, consumer perception of CSR can be an important determinant of the success of CSR practices in any organization.…”
Section: Introductionmentioning
confidence: 99%
“…Applying the concept of human values to the CSR context, prior studies have found that consumer awareness and evaluations of CSR actions are mainly determined by their own values (Basil & Weber, 2006;Golob, Lah, & Jančič, 2008;Wang & Juslin, 2012). Thus, it is plausible that consumer perception of a company's CSR quality and commitment is positively influenced when the consumers' personal values are congruent with the company's CSR goals or activities (Park et al, 2017).…”
Section: Wants and Getsmentioning
confidence: 99%